Lilium and the relative value of symptoms - Von Keller, Georg (British Homeopathic Journal, 1981)
Tape recordings are presented of a case where Lilium tigrinum provided the cure, and to begin with an attempt is made to solve the case with the aid of the repertory only, without consulting the materia medica. Lachesis emerges as the result, and not Lilium. The reason is shown to be that the short rubrics needed for repertorization are by their very nature incomplete, so that the right remedy is often excluded.Next, some highly characteristic Lilium symptoms are quoted from the provings, and these are then brought out more clearly with the aid of further tape recordings. A surprisingly close correspondence emerges of its own accord between some highly differentiated Lilium symptoms and certain symptoms presented by the patient—demonstrating the application of the “keynote system”. It is established that this system is not, in fact, in opposition to repertorization based on the totality of symptoms. Quotes from the literature show that Kent himself certainly also used keynotes to find the remedy, and was against purely mechanical repertorization.The conclusion to be drawn is that the value of a symptom in our search for the right remedy does not depend on whether it is a mental, general or local symptom, but that the really valuable symptoms are only those which are characteristic as defined in § 153 of the Organon, i.e. “More accurately described”.